Story, Metaphor, and Altruism in Cross-Cultural Teaching and Learning - Black, Michael P.; Kazama, Andy M.; Gyatso, Kalden; Dema, Thukten (Frontiers in Communication, 2022)
The Emory-Tibet Science Initiative (ETSI) is a cross-cultural exchange of Western and Tibetan Buddhist education and scholarship. In this partnership between the Dalai Lama Foundation and Emory University, two visiting Western scientists to Sera, Gaden, and Drepung Monasteries and two monastics who studied at Emory University reflect on their experiences teaching and learning from Western and Buddhist perspectives as part of the ETSI program. Specifically, authors explore the power of story, metaphor, and altruism in Buddhist and Western ways of teaching and learning. Authors consider the pedagogical similarities between 1) the variations of the Greek Method of Loci (Memory Palace) and the paintings and temple decorations found throughout Tibetan architecture and 2) the role of altruism and intrinsic motivation in learning outcomes. Current psychological and neurobiological evidence for the increased recall of episodic memories present in both Buddhist and Western use of story, metaphor, and intrinsic motivation associated with altruism will highlight the underlying principles that support these ancient methods. Finally, considerations on how each perspective informs the other is discussed, as well as practical suggestions for integrating methods across cultures.